Network authentication with time expired scheme and random generated password / Muhamad Syuhaimi Baharuddin - Baharuddin, Muhamad Syuhaimi (2004)
The project was implemented in order to reduce the problems of user's that forget the password. Basically, a lot of user uses their personal informations as the password. It increases the risk of the password to be captured through password guessing attacks or brute-force attack. So, to reduce the possibility of the attack, we replace the user password with 30 bytes random characters as the passwords. The user can recieves the password through their email. The project also provides time expires scheme that only allow the authorized user to use the system in the particular amount of time and after that, the another authentication session is required. In the next authentication session, a new password is required and the password are sent to the user's email adddresses if the user request it. This project only can reduce the risk of attack via brute-force or password guessing techniques only and not the the other types of attacks such as sniffing or Denial Of Service attack . The project just focused on the authentication process only and not the other security features.